A note about splittings of groups and commensurability under a cohomological point of view - Andrade, Maria Gorete Carreira [UNESP]; Fanti, Ermínia de Lourdes Campello [UNESP] (My University, 2010)
Let G be a group, let S be a subgroup with infinite index in G and let FSG be a certain Z2G-module. In this paper, using the cohomological invariant E(G, S, FSG) or simply E˜(G, S) (defined in [2]), we analyze some results about splittings of group G over a commensurable with S subgroup which are related with the algebraic obstruction “singG(S)" defined by Kropholler and Roller ([8]. We conclude that E˜(G, S) can substitute the obstruction “singG(S)" in more general way. We also analyze splittings of groups in the case, when G and S satisfy certain duality conditions.